(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Glial tumors of the brain in the structure of neuro-oncological diseases, despite the significant progress achieved in the diagnosis and treatment of this nosological category, still remain an urgent problem. Epidemiological data on primary tumors of the central nervous system vary from 7.42 to 13.9 per 100,000 population per year. The incidence of glial tumors is high among people of working age with rates from 40 to 65% of all tumors of the central nervous system [1,2,3,4]. Despite the advances made in the field of neurooncology, a number of issues still need to be detailed, including the use of modern methods of radiation diagnostics not only for diagnostic purposes, but also in planning surgical approaches, as well as a more detailed study of the complex treatment of glial brain tumors, which includes surgery, radiation and chemotherapy [5,6,7].